Implementation of Science Literacy in Science Study Courses for PGSD Students - Wijayaningputri , Arinta Rezty; Utami , Ima Wahyu Putri; Utami , Ima Wahyu Putr (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
In the world of Science Education, Science Literacy plays an important role in preparing quality and competent students who are able to compete at the international level. To cultivate and improve science literacy in science education, lecturers must create a learning environment that actively involves students. Learning that is dominated by lecturer-centered methods, such as lectures and textbooks, produces passive learners, which can lead to boredom and lack of reasoning and knowledge in science literacy. This study aims to explore the implementation of science literacy in the Science Study Course for PGSD students. The methodology involves literature studies, field observations, and interviews. Data were obtained through reviewing articles, journals, and other relevant sources related to the research, supported by observations and interviews, and then analyzed qualitatively through descriptive descriptions. The results of the study show: (1) the implementation of science literacy facilitates students in understanding the material presented, namely the solar system through various activities such as reading scientific texts, writing scientific essays, creative activities or making posters, searching for information, reflection, presentations, discussions, and questions and answers, (2) supporting factors in the science literacy movement are the lecturers who teach, available facilities, scientific articles, and book references.